2021
DOI: 10.5829/ije.2021.34.04a.04
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of Response of the Post-Tensioned Tapered Steel Beams with Shape Memory Alloy Tendons

Abstract: The external post-tension technique is one of the best strengthening methods for reinforcement and improvement of the various steel structures and substructure components such as beams. In the present work, the load carrying capacity of the post-tensioned tapered steel beams with external shape memory alloy (SMA) tendons were studied. 3D nonlinear finite element method with ABAQUS software is used to determine the effects of the increase in the flexural strength, and the improvement of the load carrying capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…The four-point bending test results showed that compared with the unreinforced beams, the ultimate load and flexural stiffness of the SMA/CFRP-composite-reinforced beams increased by 79.2% and 57.9%, respectively, basically equal to the sum of the effects of the SMA reinforcement alone and CFRP reinforcement alone. Hosseinnejad et al [114,115] increased the bearing capacity of steel beams by arranging pre-stressed SMA tendons outside their bodies. The analysis results show that the arrangement of SMA tendons increases the structural-load-carrying capacity more than the arrangement of steel tendons, and the pre-stressing is conveniently applied.…”
Section: Bearing Capacity Reinforcementmentioning
confidence: 99%
“…The four-point bending test results showed that compared with the unreinforced beams, the ultimate load and flexural stiffness of the SMA/CFRP-composite-reinforced beams increased by 79.2% and 57.9%, respectively, basically equal to the sum of the effects of the SMA reinforcement alone and CFRP reinforcement alone. Hosseinnejad et al [114,115] increased the bearing capacity of steel beams by arranging pre-stressed SMA tendons outside their bodies. The analysis results show that the arrangement of SMA tendons increases the structural-load-carrying capacity more than the arrangement of steel tendons, and the pre-stressing is conveniently applied.…”
Section: Bearing Capacity Reinforcementmentioning
confidence: 99%
“…Gerami [10] has investigted the steel moment frames using novel post-tensioned connections. Hosseinnejad et al [11] investigated the use of smart materials (e.g., SMA) in post-tensioned connections.…”
Section: Introductionmentioning
confidence: 99%
“…Barkhordari and Tehranizadeh [25] evaluated the effect of tuned mass damper (TMD), viscous damper, friction damper, and lead core rubber bearing in damage control and seismic response of high-rise structures equipped with a concrete shear wall. Hosseinnejad et al [26] studied the load-bearing capacity of the post-tensioned tapered steel beams by shaped memory alloy (SMA) tendons. Heydari and Gerami [27] investigated the approach of moment frames with conventional welded connections using a reversible system.…”
Section: Introductionmentioning
confidence: 99%